Design minikaravanu - Lob, Dominik (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Diplomová práce se zabývá designem exteriéru a interiéru minikaravanu. Výsledný návrh je vytvořen s ohledem na poznatky z designérské a technické analýzy a přináší osobitý designérský přístup k řešení problematiky. Hlavním cílem práce bylo vyřešit ergonomické a tvarové problémy a zpopularizovat minikaravan na evropském trhu.

The master thesis deals with the design of exterior and interior of a teardrop trailer. The final design is created in regard to knowledge from design and technical analysis and brings unique design aproach to the solution. The purpose of this work is to solve ergonomic and shaping problems and to introduce a teardrop trailer on the european market.
Design of Mini Caravan
Keywords: Karavan; přívěs; interiér; exteriér; design; Caravan; trailer; teardrop trailer; interior; exterior; design